Circulating (CD3−CD19+CD20−IgD−CD27highCD38high) Plasmablasts: A Promising Cellular Biomarker for Immune Activity for Anti-PLA2R1 Related Membranous Nephropathy?. (14th July 2016) - Pozdzik, Agnieszka; Beukinga, Ingrid; Gu-Trantien, Chunyan; Willard-Gallo, Karen; Nortier, Joëlle; Pradier, Olivier
Abstract : Membranous nephropathy (MN) is a kidney specific autoimmune disease mainly mediated by anti-phospholipase A2 receptor 1 autoantibody (PLA2R1 Ab). The adequate assessment of chimeric anti-CD20 monoclonal antibody, rituximab (RTX), efficacy is still needed to improve clinical outcome of patient with MN. We evaluated the modification of plasmablasts (CD3 − CD19 + CD20 − IgD − C D 27 h i g h C D 38 h i g h ), a useful biomarker of RTX response in other autoimmune diseases, and memory (CD3 − CD19 + CD20 + IgD − CD27 + CD38 − ) and naive (CD3 − CD19 + CD20 + IgD + CD27 − C D 38 l o w ) B cells by fluorescence-activated cell sorter analysis in PLA2R1 related MN in one patient during the 4 years of follow-up after RTX. RTX induced complete disappearance of CD19 + B cells, plasmablasts, and memory B cells as soon as day 15. Despite severe CD19 + lymphopenia, plasmablasts and memory B cells reemerged early before naive B cells (days 45, 90, and 120, resp.). During the follow-up, plasmablasts decreased more rapidly than memory B cells but still remained elevated as compared to day 0 of RTX. Concomitantly, anti-PLA2R1 Ab increased progressively. Our single case report suggests that, besides monitoring of serum anti-PLA2R1 Ab level, enumeration of circulating plasmablasts and memory B cells represents an attractive and complementary tool to assess immunological activity and efficacy of RTX induced B cells depletion in anti-PLA2R1 Ab related MN.